Generation of Single Frequency Light From an Optical Feedback Special Laser Module - Phuc, Tran Thi; Luc, Vu Van (Communications in Physics, 2008)
Generation of single frequency radiation from a semiconductor laser based on a special laser module (amplifying laser module) is presented. The multi-mode emission with the spectral bandwidth of 100A^o is converted to single mode one with a narrow bandwidth of 2A^o in the presence of external optical feedback. Wavelength tunability of the laser emission over the range of 4-10 nm is also shown. The results could be used in high speed optical communication, WDM and other applications.